The Effect Of Social Performance On Financial Performance By The Composition Of Third-Party Funds As An Intervening Variable - Harahap, Darwis (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
The background of the problem in this study is due to the incompatibility of the theory with the phenomenon that occurs in Sharia commercial banks where the theory states that if the social performance of Islamic banking increases, financial performance must also increase, but what happens to Islamic banks in 2021 is not in accordance with existing theory. The formulation of the problem in this study is whether the composition of third-party funds effectively mediates the influence of social performance on finance in Islamic banking. The purpose of this study is to determine the composition of third-party funds effectively mediating the influence of social performance on financial performance in Islamic banking.This type of research is quantitative research obtained from financial statements contained on the  Financial Services Authority (OJK) website and on the company's financial statement site. This research was conducted in the Islamic banking financial industry. Research using purposive sampling is a sampling technique with special considerations so that it is worthy of being a sample. The data analysis techniques used are Outer Model Value Evaluation, Inner Model Value Evaluation, and Effect Test Evaluation. This research was analyzed using a tool namely path analysis / PLS 3.0.Based on the results of this study, the Direct Effect test can be concluded that the Social Performance variable has no effect on the Financial Performance of Islamic Banking in Indonesia. Social Performance variables do not affect the composition of Islamic Banking Third Party Funds in Indonesia. The variable Composition of Third Party Funds does not affect the Financial Performance of Islamic Banking in Indonesia. And the variable of Third Party Fund Composition is not able to strengthen the relationship between the influence of Social Performance on Financial Performance in Islamic Banking